A Systematic Review of Arts-Based Interventions Delivered to Children and Young People in Nature or Outdoor Spaces: Impact on Nature Connectedness, Health and Wellbeing - Moula, Zoe; Palmer, Karen; Walshe, Nicola (Frontiers in Psychology, 2022)
Background The time that children and young people spend in nature and outdoor spaces has decreased significantly over the past 30 years. This was exacerbated with a further 60% decline post-COVID-19. Research demonstrating that natural environments have a positive impact on health and wellbeing has led to prescription of nature-based health interventions and green prescribing, although evidence for its use is predominantly limited to adults. Growing evidence also shows the impact of arts on all aspects of health and wellbeing. However, what has received scant attention in literature is the interconnection between the two: arts and nature. Aims This review synthesizes the literature surrounding the interconnectedness between arts and nature, and their impact on the health and wellbeing of children and young people. Methods Eight major electronic databases were systematically searched, while hand-searching included 20 journals, six books, and contact with experts. The review was conducted using the Cochrane handbook for systematic reviews, PRISMA guidelines and TIDieR template. All stages were conducted independently by two researchers and the protocol was published on PROSPERO (Registration no.: CRD42021286574). Results Although 9,314 records were identified, only 11 records were included as most studies focused either on arts or nature, but not both. Studies were conducted in United Kingdom, United States, Ireland, Australia, and Hong Kong, in a range of spaces such as forests, woodlands, beaches, parks, fields, gardens, and school playgrounds. The review encompasses data from 602 participants in total. Discussion Arts-in-nature offered an inclusive medium to engage all children and young people, especially those who might otherwise remain disinterested about environmental issues and disengaged with educational programs. Further, arts-in-nature provided stimuli to increase nature connectivity, understand environmental issues and explore ways to prevent environmental disasters. This led to higher environmental awareness and pro-environmental behaviors, and potential decrease in eco-anxiety. Conclusion Although the quality of qualitative studies was high, the quality of quantitative studies was low or unclear, thus quantitative evidence is still at its infancy. Implications for research, policy, and practice are discussed, such as methods and activities to strengthen future interventions. Scaling-up existing interventions may lead to wider recognition and inclusion of arts-in-nature in future health guidelines, including green prescribing.